Preliminary evidence of early deglaciation in southern Chile - Anderson, D. M.; Archer, R. B. (Palaeogeography Palaeoclimatology Palaeoecology, 1999)
The end of the last ice age in the channels of southern Chile is recorded by resumed sedimentation in formerly ice-filled basins. To identify the timing of initial ice retreat in Southern Chile, we examined ice-proximal sediments from a proglacial lake along the eastern margin of the Magallanes ice sheet, an environment thought to be sensitive to initial melting (Porter, S.C,, Clapperton, C.M., Sugden, D.E., 1992. Chronology and dynamics of deglaciation along and near the Strait of Magellan, southernmost South America. Sver. Geol. Unders. 81, 233-239). AMS-radiocarbon dates of the supra-till deposits in two cores indicate that sedimentation resumed 18 radiocarbon kyr. Deposition in kettle-holes and bogs on the adjacent land surfaces began at the same time or earlier (17-25 radiocarbon kyr) (Clapperton, C.M., Sugden, D.E., Kaufman, D.S., McCulloch, R.D., 1995. The last glaciation in central Magellan Strait, Southernmost Chile. Quat. Res. 44, 133-148). Our preliminary interpretation is that these events indicate initial deglaciation in the region and the formation of a large proglacial lake, followed several thousand years later by the invasion of salt water as sea level rose. Deglaciation in southers Chile occurred too early to be forced by the resumption of North Atlantic Deep Water formation, sea level rise, or northern hemisphere summer insolation, and we suggest instead that southern insolation played a role. The time of initial deglaciation in southern Chile (21-27 calendar kyr) occurred as southern hemisphere annual insolation increased from a minimum at 29 calendar kyr (6 W/m(2) less than today at 80 degrees S). (C) 1999 Elsevier Science B.V. All rights reserved.
160wbTimes Cited:13Cited References Count:25